Malignant Peripheral Nerve Sheath Tumors in Neurofibromatosis: Impact of Family History. Issue 6 (August 2018) - Malbari, Fatema; Spira, Menachem; B. Knight, Pamela; Zhu, Chong; Roth, Michael; Gill, Jonathan; Abbott, Rick; Levy, Adam S.
Abstract : Objective: The main objective of this study was to determine if family history of malignant peripheral nerve sheath tumor (MPNST) increases risk of developing an MPNST in patients with neurofibromatosis-1 (NF-1). Materials and Methods: Individuals with NF-1 registered with the Children's Tumor Foundation's Neurofibromatosis Registry were emailed an anonymous 15-minute survey with regard to personal and family history of NF-1, MPNST, ages of onset, and symptomatology. Participation was voluntary and information was self-reported. Results: The survey was sent to 4801 registrants, 878 responded. Presence of a family history of MPNST was found to be a risk factor for the development of MPNST; 19.4% of respondents confirming a family history of MPNST developed MPNST compared with 7.5% of respondents with no family history (odds ratio, 2.975; 95% confidence interval, 1.232-7.187; P =0.021). NF-1 patients with a positive family history developed MPNST at a younger age than those with no family history (8.3% vs. 0.5% P =0.003 and 13.9% vs. 2.4% P =0.003, for onset before 10 and 20, respectively). In the MPNST population with a known family history, onset prior to age 10 was significantly more prevalent (42.9% vs. 7% P =0.029). Conclusions: These results suggest a positive family history of MPNST represents a risk factor for the development and early onset of MPNST in individuals with NF-1. Abstract : Supplemental Digital Content is available in the text.